TPP: A win for ASEAN, A loss for WTO? - Pitakdumrongkit, Kaewkamol (2015)
With the TPP being concluded, what will be its impact on the regional and global levels? The TPP’s effect on ASEAN states depends on whether the countries are part of the deal as well as their respective domestic policies. The burden is now on the WTO to stay relevant.